Mesospheric Nitric Acid Enhancements During Energetic Electron Precipitation Events Simulated by WACCM-D - Orsolini, Yvan J.; Smith-Johnsen, Christine; Marsh, Daniel R.; Stordal, Frode; Rodger, Craig J.; Verronen, Pekka T.; Clilverd, Mark A. (Journal of Geophysical Research: Atmospheres, 2018)
While observed mesospheric polar nitric acid enhancements have been attributed to energetic particle precipitation through ion cluster chemistry in the past, this phenomenon is not reproduced in current whole-atmosphere chemistry-climate models. We investigate such nitric acid enhancements resulting from energetic electron precipitation events using a recently developed variant of the Whole Atmosphere Community Climate Model (WACCM) that includes a sophisticated ion chemistry tailored for the D-layer of the ionosphere (50–90 km), namely, WACCM-D. Using the specified dynamics mode, that is, nudging dynamics in the troposphere and stratosphere to meteorological reanalyses, we perform a 1-year-long simulation (July 2009–June 2010) and contrast WACCM-D with the standard WACCM. Both WACCM and WACCM-D simulations are performed with and without forcing from medium-to-high energy electron precipitation, allowing a better representation of the energetic electrons penetrating into the mesosphere. We demonstrate the effects of the strong particle precipitation events which occurred during April and May 2010 on nitric acid and on key ion cluster species, as well as other relevant species of the nitrogen family. The 1-year-long simulation allows the event-related changes in neutral and ionic species to be placed in the context of their annual cycle. We especially highlight the role played by medium-to-high energy electrons in triggering ion cluster chemistry and ion-ion recombinations in the mesosphere and lower thermosphere during the precipitation event, leading to enhanced production of nitric acid and raising its abundance by 2 orders of magnitude from 10−4 to a few 10−2 ppb.
Keywords: Antarktis; elektroner; energiske partikler; geomagnetiske stormer; geovitenskap; ionosfæren; klimamodeller; meteorologi; polarområdene; salpetersyre; stratosfæren

Global Cooling Contributed to the Establishment of a Modern-Like East Asian Monsoon Climate by the Early Miocene - Zhang, Ran; Zhang, Zhongshi; Jiang, Dabang (Geophysical Research Letters, 2018)
The establishment of a modern-like monsoon climate in East Asia by the early Miocene was a complex process forced by several factors, and previous studies paid less attention to global cooling. Here we investigate this process using climate modeling by considering changes in topography and global cooling under the early Miocene boundary conditions. Using early Miocene paleogeography and an atmospheric CO2 concentration of 560 ppmv, our model results indicate that a nonzonal climate pattern has appeared in East China but that this climate exhibits weak precipitation and wind seasonality. Such seasonality strengthens as the concentration of atmospheric CO2 decreases from 560 to 420 ppmv and resembles the modern-like condition after the growth of the Antarctic ice sheet. Although the development of East Asian topography can further strengthen this seasonality, our results indicate that global cooling is also pivotal for the establishment of a modern-like monsoon climate in East Asia.
Keywords: Antarktis; innlandsis; klimamodeller; klimatologi; nedbør; paleogeografi